An Analysis of Swear Words Used by Netizens Comments in Lutfi Agizal Instagram Account - Zonelia, Karmila; Refnaldi, Refnaldi (English Language and Literature, 2023)
In society, people communicate and show emotion in different ways. Currently, it is often found that people express their feeling and emotion in swearing. This study aims to find out the categories of swear word used by netizens comments in Lutfi Agizal’s Instagram account. This research used a theory by Hughes(1996). This study is descriptive research. The data were taken from 21 posts in Lutfi Agizal’s account from August up to October 2020. The result shows that from 90 data collected, there are six categories out of swear word that have been found from seven categories of Hughes’s theory. They are religion (15.58%), genitalia (10.66%), excretion (5.73%), stupidity (17.21%), animal term (33.61%), and general (17.21%), while anatomical insult is not found from the data. By the finding, it can be concluded that the most dominant used of swear word is animal term.